Antidiabetic Test of Ethanolic Extract of Ant Nest Plants (Myrmecodia sp.) Against the -Glucosidase Enzyme In Vitro - Daniel, Daniel; Isa, Muhammad; Hasan, Muhammad; Sari, Wahyu Eka; Rosmaidar, Rosmaidar; Aisyah, Siti; Athaillah, Farida; Frengki, Frengki (Jurnal Medika Veterinaria, 2024)
The use of plants, one of the biological sources, as an alternative medicine for degenerative diseases is increasingly being studied. Usually, the biological effects of these plants come from the secondary metabolite components contained therein. Ant nest is one of them which is reported to contain compounds belonging to the class of flavonoids, tannins, and polyphenols. This research was conducted in vitro by observing the antidiabetic potential of the ethanolic extract of ant nests against the -glucosidase enzyme following the modified "Wako Pure Chemical Industries Ltd., Japan" protocol. The results showed that the inhibitory power of -glucosidase of the extract was stronger than that of the quercetin control with IC50 values of 10.59 g/mL and 38.09 g/mL, respectively. These results proved that the ethanolic extract of ant nest had very strong -glucosidase inhibitory property. Predictive analysis of the pharmacokinetics and toxicity of the bioactive compounds contained in the ant nest extract showed that rutin has similar characteristics to acarbose as a first-line anti-diabetic drug of choice through an -glucosidase inhibitor mechanism, so rutin is worthy of consideration for development as an anti-diabetic candidate.